Perspektif Soteriologi dalam Alkitab sebagai Perjanjian - Dea Okta Florenzia; Shinta Shinta; Berkat Ricart Dwi Putra; Sarmauli Sarmauli (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Soteriology is the doctrine or teaching about salvation. Which was done by God in and through Jesus Christ. The Triune God fulfills the covenant of salvation to save humans. God the Father who plans and determines the conditions (sends), God the Son who fulfills the conditions (sent), and the Holy Spirit who gives the fruit of salvation to humans. God the Son willingly was able to do it. This research aims to provide broader insight into the perspective of salvation as a covenant, conditions and steps in the Bible. This research is qualitative research, using the literature study method.